2022
DOI: 10.1007/s00542-022-05350-4
|View full text |Cite
|
Sign up to set email alerts
|

Injection moulding of micropillar arrays: a comparison of poly(methyl methacrylate) and cyclic olefin copolymer

Abstract: Injection moulding of micropillar arrays offers a fast and inexpensive method for manufacturing sensors, optics, lab-on-a-chip devices, and medical devices. Material choice is important for both the function of the device and manufacturing optimisation. Here, a comparative study of poly(methyl methacrylate) (PMMA) and cyclic olefin copolymer (COC) injection moulding of micropillar arrays is presented. These two polymers are chosen for their convenient physical, chemical, and optical properties, which are favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Second, each component of the platform can potentially be miniaturized and integrated for POC applications. For instance, the microfluidic pillar array can be mass-produced by using thermoplastics via injection molding . The optical system with bulky instrumentation can be simplified by using compact laser diodes as the light source and intensity-based photodetectors for low-cost read-outs .…”
Section: Resultsmentioning
confidence: 99%
“…Second, each component of the platform can potentially be miniaturized and integrated for POC applications. For instance, the microfluidic pillar array can be mass-produced by using thermoplastics via injection molding . The optical system with bulky instrumentation can be simplified by using compact laser diodes as the light source and intensity-based photodetectors for low-cost read-outs .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of PP molded parts, which yielded the highest replication for the different textures, Insert C demonstrated a 39% increase when turned, while Insert D demonstrated a 53% increase. The PMMA samples showed a similar growth trend, but not as significant, due to the lack of molecular movements when molded at 80 • C. The flow was less inhibited when the parallel trench microstructures were parallel to the flow direction [45].…”
Section: Replication Of Feature Heightmentioning
confidence: 87%
“…11 The warping and shrinkage distortion of the molded part could be effectively avoided by selecting right parameters. 12,13 By analyzing the molding quality of polymethyl methacrylate (PMMA) and cyclic olefin copolymer (COC) micropillar arrays under different parameters, Priest et al 14 analyzed the molding quality of PMMA and COC micropillar arrays under varying parameters, discovering that the lower surface energy of COC facilitated easier demolding without microstructural fractures. Fan et al 15 showed that in addition to mold design, injection pressure, injection speed, and melt temperature needed to be carefully adjusted to meet the requirements.…”
Section: Introductionmentioning
confidence: 99%